Ocean circulation changes drive shifts in Calanus abundance in North Atlantic right whale foraging habitat: A model comparison of cool and warm year scenarios. (September 2021) - Brennan, Catherine E.; Maps, Frédéric; Gentleman, Wendy C.; Lavoie, Diane; Chassé, Joël; Plourde, Stéphane; Johnson, Catherine L.
Highlights: Prey transport to sGSL right whale foraging habitat shaped by runoff, wind, warming. Model simulates Cool & Warm Year C. finmarchicus & C. hyperboreus spatial patterns. Advection dominates southern GSL Calanus influx variability in spring-early summer. GSL C. finmarchicus population declines drive late summer-fall variability. Large upstream population declines on the Scotian Shelf dominate at Roseway Basin. Abstract: Starting 2010, declines in Calanus finmarchicus and Calanus hyperboreus, the biomass dominant copepods on the northwest Atlantic shelf, coincide with notable ocean warming and a northward shift in endangered North Atlantic right whale ( Eubalena glacialis ) foraging habitat from the Bay of Fundy/Western Scotian Shelf to the southern Gulf of St. Lawrence (sGSL). Abundance changes in right whales' prey, lipid-rich Calanus late stages, are known to relate to shifts in Calanus demography and changes in Calanus transport. Our objective was to investigate how these mechanistic drivers shaped potential whale preyscapes during the relatively cooler, high-abundance 2000′s vs the warmer, lower abundance 2010′s. Here, bio-physical Calanus model "Cool Year" and "Warm Year" simulations are used to quantify relative effects of the physical environment vs population level. Analysis is focused on the western sGSL, where right whales have recently been observed foraging in high numbers. Simulations indicate that Calanus variability is most strongly influenced by changes in advection from upstream areas, linked to river runoff and winds on the coastal Gaspé Current in late spring and summer. In the simulated Cool Year (2008), high runoff is associated with a strong Gaspé Current hugging the coastline and advection of Calanus into the western sGSL. Conversely, in the simulated Warm Year (2012), lower runoff led to a separation of the Gaspé Current from the coast, transporting Calanus eastward along the Laurentian Channel, away from Shediac Valley. Variation in population size drives changes in late stage Calanus delivery to the western sGSL in late summer and fall. Complementary analyses on the Western Scotian Shelf indicate that the source of Calanus to Roseway Basin can shift between the coastal Nova Scotia Current and Scotian Shelf slope water, but large declines in upstream population drive lower Warm Year abundance. Our findings inform marine managers about how Calanus high abundance areas may continue to change in the future.